A solution to the cooling and preheating of hydraulic system by organic Rankine cycle with heat pump. (15th January 2019) - Gu, Zhengzhao; Zhang, Xiaogang; Dong, Zhixin; Quan, Long
Highlights: An organic Rankine cycle with heat pump system is proposed for hydraulic systems. The proposed system applied to a 260-ton hydraulic excavator is investigated. The optimal working fluid for the proposed system is selected. The earning of equilibrium temperature shows a maximum at certain oil temperatures. The economic performance decreases with the increase in ambient temperature. Abstract: The operating temperature of hydraulic oils should be controlled within a reasonable range to keep hydraulic systems in good working condition. However, due to the huge energy losses of hydraulic systems, the oil temperature will increase rapidly. In addition, some hydraulic equipment often operate in cold weather conditions. The conventional cooling with radiators and preheating with electric heaters will consume extra energy for hydraulic systems. Therefore, an organic Rankine cycle with heat pump system is proposed to achieve regenerative cooling and energy-efficient preheating. The system can operate in two modes: an organic Rankine cycle mode to produce electricity instead of consuming energy while cooling the hot oil, and a heat pump mode to preheat the oil with less energy before the hydraulic system starts up in a cold environment. The system is applied to a 260-ton hydraulic excavator to investigate the technical feasibility. On average, the calorific power of the excavator is 177 kW at 245 kW of consumed power in a typical cycle. Considering the cost of heat source, the earning of equilibrium temperature is proposed to evaluate the benefit of the organic Rankine cycle. The optimal working fluid is selected by comparing the system performance. Afterward, the peak points of earning of equilibrium temperature at different ambient temperatures are observed. Corresponding to the maximum earning of equilibrium temperature, the output power of the organic Rankine cycle ranges from 7.63 kW to 2.89 kW. These results show significant energy savings by applying the proposed system in the hydraulic system.